PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BEI TAHUN 2020-2022 - Azizah Putri Az-Zahra; Desy Nur Pratiwi; Wikan Budi Utami (Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the effect of inflation, interest rates and exchange rates on share prices in manufacturing companies listed on the IDX.  The objects studied in this research are basic material companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This type of research is quantitative research. The research sample was selected using a purposive sampling technique and obtained 144 observation data. This research uses secondary data obtained through the Indonesian Stock Exchange and Bank Indonesia websites. The data analysis technique in this research is multiple linear regression. The research results show that the Inflation variable has no effect on Stock Prices, while the Interest Rate and Exchange Rate variables have an effect on Stock Prices.